Assessment and outcome of pediatric intestinal pseudo-obstruction: A tertiary-care-center experience from Turkey - Yeliz Çağan Appak; Maşallah Baran; Mustafa Onur Öztan; Miray Karakoyun; Soysal Turhan; Cem Tuğmen; Sema Aydoğdu; Cezmi Karaca; Gökhan Köylüoğlu (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Pediatric intestinal pseudo-obstruction (PIPO) is a severe disorder of gut motility. In this rare and difficult-to-manage disease, complex treatment method, such as intestinal transplantation, is sometimes needed. This study evaluated the management and follow-up results of patients with PIPO who received treatment at our center. Materials and Methods: The cases of 13 patients with PIPO were reviewed retrospectively. Demographic data, clinical features, etiologies, pharmacological and surgical treatments, nutritional support, anthropometric findings, small bowel transplantation (SBT), and survival rates were assessed. Results: Two of the patients were diagnosed at 1 and 5 years of age, while other patients were diagnosed during neonatal period. The etiological cause could not be identified for 5 patients. Pharmacological treatment response was observed in 38.4% of patients. Post-pyloric feeding was applied in 4 patients, but no response was observed. Gastrostomy decreased the clinical symptoms in 3 patients during the abdominal distension period. Total oral nutrition was achieved in 38.4% of the total-parenteral-nutrition (TPN)-dependent patients. It was observed that anthropometric findings improved in patients with total oral nutrition. Liver cirrhosis developed in 1 patient. Venous thrombosis developed in 4 patients. The SBT was performed on 3 patients. One of these patients has been followed up for the last 4 years. Conclusion: Pediatric intestinal pseudo-obstruction is a rare disease that can present with a wide range of clinical symptoms. While some patients require intestinal transplantation, supportive care may be sufficient in others. For this reason, patients with PIPO should be managed individually. Cite this article as: Çağan Appak Y, Baran M, Öztan MO, et al. Assessment and outcome of pediatric intestinal pseudo-obstruction: A tertiary-care-center experience from Turkey. Turk J Gastroenterol 2019; 30(4): 357-63.